2018
DOI: 10.1002/mds.27474
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term GPi‐DBS improves motor features in myoclonus‐dystonia and enhances social adjustment

Abstract: Background Good short‐term results of pallidal deep brain stimulation have been reported in myoclonus‐dystonia. Efficacy and safety in the long term remain to be established. In addition, the actual impact of DBS treatment on social inclusion is unknown. The objective of this study was to assess the long‐term clinical outcome, quality of life, and social adjustment of GPi‐DBS in patients with ε‐sarcoglycan (DYT11)‐positive myoclonus‐dystonia. Methods Consecutive myoclonus‐dystonia patients with ε‐sarcoglycan m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…Interestingly, DBS of the internal globus pallidus (GPi) results in a dramatic and sustained improvement of both myoclonus and dystonia. This suggests that dysfunction of the striato‐pallido‐thalamo‐cortical network is critically involved in the generation of this motor phenotype . Metabolic neuroimaging and various neurophysiological studies point to a dysfunctional cerebello‐thalamo‐cortical pathway .…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, DBS of the internal globus pallidus (GPi) results in a dramatic and sustained improvement of both myoclonus and dystonia. This suggests that dysfunction of the striato‐pallido‐thalamo‐cortical network is critically involved in the generation of this motor phenotype . Metabolic neuroimaging and various neurophysiological studies point to a dysfunctional cerebello‐thalamo‐cortical pathway .…”
mentioning
confidence: 96%
“…This suggests that dysfunction of the striato-pallido-thalamo-cortical network is critically involved in the generation of this motor phenotype. [20][21][22] Metabolic neuroimaging and various neurophysiological studies point to a dysfunctional cerebello-thalamocortical pathway. [23][24][25] Similar to other dystonic syndromes, 26 abnormal sensorimotor integration with hypoactivity within the premotor, sensory, and parietal cortices and the cerebellum has been shown in DYT-SGCE.…”
mentioning
confidence: 99%
“…Intriguingly, GPi and Vim DBS had comparable beneficial effects on myoclonus, whereas improvement in dystonia was greater with GPi than Vim DBS. A recent prospective study showed the long-term efficacy of GPi DBS both on myoclonus and dystonia at a mean follow-up of 8.7 years [55].…”
Section: Inherited Combined Dystoniamentioning
confidence: 99%
“…There is no treatment that addresses the underlying cause of MD; therefore, treatment is entirely symptomatic. In recent years, deep brain stimulation (DBS) has shown significant promise in treating these patients [6,7]. Although patients with myoclonus or dystonia as the sole clinical feature have been described [8], there is only one report in the literature of a patient with positive SGCE mutation and isolated myoclonus phenotype who has been treated with DBS of the globus pallidus internus (GPi) [9].…”
Section: Introductionmentioning
confidence: 99%